Lipopolysaccharide-Induced Weakness in the Preterm Diaphragm Is Associated with Mitochondrial Electron Transport Chain Dysfunction and Oxidative Stress - Song, Yong; Pinniger, Gavin J.; Bakker, Anthony J.; Moss, Timothy J. M.; Noble, Peter B.; Berry, Clare A.; Pillow, Jane J. (PLOS ONE, 2013)
Diaphragmatic contractility is reduced in preterm lambs after lipopolysaccharide (LPS) exposure in utero. The mechanism of impaired fetal diaphragm contractility after LPS exposure is unknown. We hypothesise that in utero exposure to LPS induces a deficiency of mitochondrial complex activity and oxidative damage in the fetal diaphragm. To test this hypothesis, we used a well-established preterm ovine model of chorioamnionitis: Pregnant ewes received intra-amniotic (IA) saline or 10 mg LPS, at 2 d or 7 d prior to surgical delivery at 121 d GA (term = 150 d). The fetus was killed humanely immediately after delivery for tissue sampling. Mitochondrial fractions were prepared from the isolated diaphragm and mitochondrial electron transfer chain activities were evaluated using enzymatic assays. Oxidative stress was investigated by quantifying mitochondrial oxidative protein levels and determining antioxidant gene and protein (catalase, superoxide dismutase 2 and glutathione peroxidase 1) expression. The activity of the erythroid 2-related factor 2 (Nrf2)-mediated antioxidant signalling pathway was examined by quantifying the Nrf2 protein content of cell lysate and nuclear extract. A 2 d LPS exposure in utero significantly decreased electron transfer chain complex II and IV activity (p<0.05). A 7 d LPS exposure inhibited superoxide dismutase 2 and catalase expression at gene and protein levels, and Nrf2 pathway activity (p<0.05) compared with control and 2 d LPS groups, respectively. Diaphragm mitochondria accumulated oxidised protein after a 7 d LPS exposure. We conclude that intrauterine exposure to LPS induces mitochondrial oxidative stress and electron chain dysfunction in the fetal diaphragm, that is further exacerbated by impairment of the antioxidant signalling pathway and decreased antioxidant activity.